"Note how for each (x,y) pair of points given we see that x*y = 60
For instance, the point (4,15) has x = 4 and y = 15 so x*y = 4*15 = 60
Another example: (x,y) = (6,10) means x = 6 and y = 10, so x*y = 6*10 = 60
The fact that this is true for ALL of the points shown indicates we have an inverse variation of the form x*y = k where k = 60 in this case.
Therefore, the answer is B.) An inverse function is the best model because the products of corresponding x- and y-values are equal."
Let the number = x
Then, it would be: (x*36)/100 = 108
x*36 = 10800
x = 10800/36
x = 300
<em>Note: As you may have unintentionally missed to add the different answers, based on which we had to check who solved correctly between Tamara and Clyda's work. </em>
<em>But, I am actually solving the expression and you must note that whoever (between Tamara and Clyda's work) may have got the same answer or match the answer with mine, would be the one who solved correctly.</em>
Answer:
We conclude that whoever (between Tamara and Clyda's work) may have got the answer as
after dividing
by
, would be the one who solved it correctly.
Step-by-step explanation:
Considering the expression
![2x^4\:+\:7x^3\:-\:18x^2\:+\:11x\:-\:2](https://tex.z-dn.net/?f=2x%5E4%5C%3A%2B%5C%3A7x%5E3%5C%3A-%5C%3A18x%5E2%5C%3A%2B%5C%3A11x%5C%3A-%5C%3A2)
Lets divide the expression by ![2x^2\:-\:3x\:+\:1](https://tex.z-dn.net/?f=2x%5E2%5C%3A-%5C%3A3x%5C%3A%2B%5C%3A1)
Solution Steps:
![\frac{2x^4+7x^3-18x^2+11x-2}{2x^2-3x+1}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E4%2B7x%5E3-18x%5E2%2B11x-2%7D%7B2x%5E2-3x%2B1%7D)
Factorizing
![\frac{\left(x-1\right)\left(2x-1\right)\left(x^2+5x-2\right)}{2x^2-3x+1}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cleft%28x-1%5Cright%29%5Cleft%282x-1%5Cright%29%5Cleft%28x%5E2%2B5x-2%5Cright%29%7D%7B2x%5E2-3x%2B1%7D)
Factorizing
![2x^2-3x+1:\quad \left(2x-1\right)\left(x-1\right)](https://tex.z-dn.net/?f=2x%5E2-3x%2B1%3A%5Cquad%20%5Cleft%282x-1%5Cright%29%5Cleft%28x-1%5Cright%29)
![\frac{\left(x-1\right)\left(2x-1\right)\left(x^2+5x-2\right)}{\left(2x-1\right)\left(x-1\right)}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cleft%28x-1%5Cright%29%5Cleft%282x-1%5Cright%29%5Cleft%28x%5E2%2B5x-2%5Cright%29%7D%7B%5Cleft%282x-1%5Cright%29%5Cleft%28x-1%5Cright%29%7D)
![\mathrm{Cancel\:}\frac{\left(x-1\right)\left(2x-1\right)\left(x^2+5x-2\right)}{\left(2x-1\right)\left(x-1\right)}:\quad x^2+5x-2](https://tex.z-dn.net/?f=%5Cmathrm%7BCancel%5C%3A%7D%5Cfrac%7B%5Cleft%28x-1%5Cright%29%5Cleft%282x-1%5Cright%29%5Cleft%28x%5E2%2B5x-2%5Cright%29%7D%7B%5Cleft%282x-1%5Cright%29%5Cleft%28x-1%5Cright%29%7D%3A%5Cquad%20x%5E2%2B5x-2)
![x^2+5x-2](https://tex.z-dn.net/?f=x%5E2%2B5x-2)
Thus,
![\frac{2x^4+7x^3-18x^2+11x-2}{2x^2-3x+1}=x^2+5x-2](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E4%2B7x%5E3-18x%5E2%2B11x-2%7D%7B2x%5E2-3x%2B1%7D%3Dx%5E2%2B5x-2)
Therefore, we conclude that whoever (between Tamara and Clyda's work) may have got the answer as
after dividing
by
, would be the one who solved it correctly.
Keywords: expression, division
Learn more about expression division from brainly.com/question/1575482
#learnwithBrainly
The base-10 value of 10510 is equal to base-2 value of 11010012. Brainliest
The answer is 0.125....................................